Design of security mechanism for communication networks in smart grid - Gurbakshish Singh Toor (2016)
The evolution of the traditional electricity infrastructure into smart grids promises more reliable and efficient power management, more energy aware consumers and inclusion of renewable sources for power generation. These fruitful promises are attracting initiatives by various nations all over the globe in various fields of academia. However, this evolution relies on the advances in the information technologies and communication technologies and thus is inevitably prone to various risks and threats. Even though many solutions have been proposed in the recent literature to overcome the security threats in smart grid networks, many issues still need to be addressed to make smart grids a reliable and efficient innovation. In this thesis, we first introduce the background, network architecture, security threats and the security requirements of smart grid networks. Our work focuses on the security aspects of Neighborhood Area Network (NAN) subsystems of smart grid. We present some of the prominent threats and attacks, specific to this subsystem, which violate the specific security goals requisite for its reliable operation. The proposed solutions and countermeasures for these security issues presented in the recent literature have been deeply reviewed to identify the promising solutions with respect to the specific security goals. Then we propose an improved dynamic key refreshment strategy for mesh security in the NAN and an authentication scheme based on software defined network (SDN) using dynamic one-way accumulators. The proposed dynamic key refreshment scheme can protect the mesh network system based on IEEE 802.11s standard from DoS attacks during the key refreshment whereby the intruder could launch the attack using the information from previous key refreshment cycle as proposed in the original key refreshment scheme. The use of simple hash based operation makes the scheme cost effective for the resource limited network devices. The proposed scheme also adds an enhancement to the sub-protocol of the original key refreshment scheme for enhanced security and reliability. The proposed SDN based authentication scheme employs one-way dynamic accumulators combined with zero-knowledge proofs for easy and cost efficient authentication process. The availability of the cross authentication among different NAN devices enables us to replicate the mesh network architecture. Using SDN as the backbone of the scheme helps us accommodate the advances of the upcoming wireless technologies where we can update the changes in the scheme conveniently. Our analysis shows that the proposed schemes can achieve the requisite authentication while withstanding multiple attacks and the balance between security and system performance is also achieved.